The relationship between barber knowledge an microbial infections from device used of beauty salons in Gonabad, Iran - Seyed Ali Sajjadi; Afsane Chavoshani; Alireza Mohamadzade; Mozhgan Chavoshani (Gonabad University of Medical Sciences, 2015)
Different factors increase risk of disease transmission in beauty salons and respect to its health conditions of barber, place and devices, as the major preventive factors, play an important role in the control of disease transmission. Hence the main purpose of this study was to evaluate effective factors on health and microbial conditions in Gonabad beauty salons in Iran. In a cross-sectional study, 73 beauty‌ salons were randomly selected. Data were compiled using a valid and reliable questionnaire, observation, interview, informal inspection of workplace and recording results of microbial cultures from device involved. The collected data were analyzed with SPSS software, version 16 ‌and descriptive statistics. Personal health index of barbers was 79.45% good and acceptable. In 89.03% of them, device health index was good and acceptable. Positive results of bacteria and fungi infections were more in who had low work experience, low literacy level and low occupational satisfactory. Non Staphylococcus aurous and Non Candida albicans were the main bacterial and fungi contaminations respectively. According to these results, improve health conditions in the barbershops, training on proper disinfection techniques, promotion of more application of disinfectants and avoid of unhealthy behaviors in beauty salons were suggested.